Beyond the Boundary of Healthcare Systems: Can Social Capital Complement Health Outcomes of the Aging? (Bangladesh Journal of Public Administration, 2020)
This paper delves into the association between social capital and health outcomes of the aging in Bangladesh. Methodological triangulation was used to synthesize primary data in this study. The data were collected based on a sample survey from 310 aging people in the aged ≥ 60 years in 2016. Findings reveal that social networks, norms of reciprocity, trust, neighborhood social cohesion and civic participation, and economic hardship are associated with self rated health status. The aging who had low social networks, norms of reciprocity and neighborhood cohesion and economic hardship were 1.917, 2.354, 2.185, and 1.949 times more likely to say that they had poor self rated health status. The synergy index between low social network and economic hard ship, low norm of reciprocity and economic hardship and low neighborhood cohesion were1.592 and 1.939 and, 2.067 supported that effect of joint exposure (low social capital and presence of economic hardship) is greater than the effect predicted from the sum of effects of each factor acting separately. The study concludes that economic hardship reduction is more important to access health care. Keywords: Social capital, healthcare systems, economic hardship, self rated health, health outcomes, interaction effects